Defining the Ca 125 value to predict optimal cytoreduction in patients with epithelial ovarian cancer - Medina Bueno, Gonzalo Arturo (2023)
Objective: To define the Ca 125 value to predict optimal cytoreduction in patientswith epithelial ovarian cancer. Methods: Observational, analytical and retrospectivestudy of 52 consecutive patients who had surgical intervention for clinical stage IIIand IV epithelial ovarian cancer and who did not receive preoperative chemotherapy.These patients were attended between January 2014 and December 2018 in theGynecology Service of the Carlos Alberto Seguín Escobedo Hospital, Arequipa, Peru.Sensitivity, specificity, positive and negative predictive value, and the area under theROC curve of the most appropriate Ca 125 cutoff point for optimal cytoreductionwere determined. Results: The patients were on average 58 years old, the seroushistologic subtype was the most frequent with 73.1%; clinical stage IIIC correspondedto 65.4% of cases and optimal cytoreduction was achieved in 61.5% of patients.The ROC curve reached 78% with Ca 125 of 716.7 U/mL as the best cut-off pointfor predicting optimal cytoreduction, with sensitivity of 75%, specificity 75%, positivepredictive value 82.8% and negative predictive value 65.2%. Conclusion: The tumormarker Ca 125 was useful in the prediction of optimal cytoreduction in patients whounderwent surgery for epithelial ovarian cancer, with the best cut-off point being716.7 U/mL.